The Women of Chicago Public Housing. Architects of their Own ‘Homeplace’ - Siefert, Rebecca (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
The story of public housing in Chicago, and the rest of the United States for that matter, tends to fixate on negative images of housing projects built between c. 1940-1960, like Cabrini-Green or Wentworth Gardens. Now that so many of the buildings have been demolished (or “redeveloped”) and scholars, institutions, and the general public have begun to untangle the complexity of the history of public housing in the U.S., it is time to move beyond the damaging narratives and negative imagery to better understand how women persevered and adapted to ensure they and their families not only had basic needs met, but also had access to safe spaces, key facilities, and opportunities for community-building, joy, and pride in their home. This paper explores connections between issues of architecture and the impact of women on the design and reform of Cabrini-Green, Wentworth Gardens, and other key examples, to demonstrate how women residents helped shape the built environment of public housing in Chicago through organizing, activism, and the appropriation of space based on everyday needs and use. Through an analysis of photographs documenting the interiors of Cabrini-Green and using a theoretical framework that combines feminist theorist bell hooks’ notion of the ‘homeplace’ as a ‘site of resistance’ (1990) with architectural historian Dell Upton’s concept of the ‘cultural landscape’ (1991), this paper proposes that we modify our current definition of an “Architect” and in fact consider these public housing residents ‘architects of their own homeplace’.
Keywords: Women Architects; Space Appropriation; Activism; Alternative Professionals; Feminist Practices